Chest Physiotherapy on the Respiratory Mechanics and Elimination of Sputum in Paralyzed and Mechanically Ventilated Patients With Acute Lung Injury: A Pilot Study - Minhee Suh, RN, PhD; Margaret Heitkemper, RN, PhD, FAAN; Choi-Kwon Smi, RN, PhD (Elsevier, 2011)
Chest physiotherapy (CPT) is commonly used for mechanically ventilated patients, but little is known about its physiological effects, particularly in patients with acute lung injury (ALI). The aim of the study was to determine the benefits and risks of delivering multimodal respiratory physiotherapy to mechanically ventilated patients with ALI receiving paralytic agents. Methods: A repeated measure-experimental design using a counterbalancing method was employed. Fifteen patients received CPT (vibration, percussion, or palm-cup percussion) in addition to the routine CPT in a randomized order. Another 15 patients, contraindicated for the percussion technique, received routine CPT including manual hyperinflation and position change, and were observed as a comparative group. The effects of CPT were evaluated by measuring the volume of aspirated secretions and the dynamic lung compliance (Cd) over time. For the adverse effects, peripheral oxygen saturation (SpO2) was recorded. Cd and SpO2 were recorded at the baseline period, immediately after the physiotherapy treatment, and at 10, 20, 30 and 60 minutes posttreatment. Results: The volume of collected secretions did not differ significantly when compared between the groups (p = .838). Cd increased significantly over time in the manual percussion (p = .042) and palm-cup percussion (p = .046) group, where Cd in the latter remained elevated twice longer than in the former. None of the CPT techniques exerted major detrimental effects on SpO2. Conclusions: We found that the palm-cup percussion technique was the most effective in increasing Cd without any accompanying detrimental effects on SpO2. However, additional CPT did not affect the volume of aspirated secretions.